Ethanol solvent and pH effect on antioxidant activity of purple sweet potato (Ipomoea batatas L.) - Adlina, Salsabila; Herdianti, Nita; Amin, Saeful; Nurzaman, Mochamad Herdi (Universitas Ahmad Dahlan, 2025)
Air pollution induces the production of reactive oxygen species (ROS), which can cause tissue damage when excessive. Antioxidants help counteract this damage, and purple sweet potatoes, rich in anthocyanins, are a promising natural antioxidant source. This study aimed to determine the effect of solvent acidity variations on the antioxidant activity of purple sweet potato (PSP) tuber extract and identify the optimal pH condition. Using the DPPH (2,2-diphenyl-1-picrylhydrazyl) scavenging assay, ethanol solvents at different pH levels (non-acidified ethanol, pH 2.5, pH 2, and pH 1.5) were tested. The results showed that higher acidity enhanced antioxidant activity, with the strongest activity observed at pH 1.5, yielding an IC50 value of 9.74±0.23 ppm. Although less potent than Vitamin C (IC50 1.22±0.04 ppm), the extract demonstrated significant potential as a natural antioxidant source. Further studies on anthocyanin content are recommended to better understand its contribution to antioxidant activity.